Insulin-Producing Cell Transplantation Platform for Veterinary Practice - Kuncorojakti, Suryo; Srisuwatanasagul, Sayamon; Kradangnga, Krishaporn; Sawangmake, Chenphop (Frontiers in Veterinary Science, 2020)
Diabetes mellitus (DM) still becomes a global concern both in human and veterinary medicine. Type I DM requires prolong and consistent exogenous insulin administration to address hyperglycemia that can increase the risk of diabetes complications such as retinopathy, nephropathy, neuropathy, and heart disorder. The successful of cell-based therapy in human medicine by the establishment of Edmonton protocol possibly were adapted in veterinary clinical application. It can maintain production of endogenous insulin and stabilize the blood glucose. The limited number of cadaveric pancreas donors and the long-term use of immunosuppressive agents are the main obstacles for this protocol. The development of potential therapy for DM during the past decade has mainly focused on the generation of effective insulin-producing cells from various sources of stem cells that can be transplanted into the body. Another approach for successful stem cell application in type I DM therapy was aimed toward the effective method to transplant generated insulin-producing cells (IPCs). Encapsulation can be offered as an alternative strategy to protect the IPCs from the body rejection due to their immunoisolation properties. In this review, current concepts of IPCs and encapsulation technology for veterinary clinical application are summarized and will provide basic concept of an up-to-date potential stem cell based platform for veterinary diabetic regenerative therapy.